2014
DOI: 10.1371/journal.pone.0114104
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of MEOX2 and TWIST1 Is Associated with H3K27me3 Levels and Determines Lung Cancer Chemoresistance and Prognosis

Abstract: Lung cancer is the leading cause of death from malignant diseases worldwide, with the non-small cell (NSCLC) subtype accounting for the majority of cases. NSCLC is characterized by frequent genomic imbalances and copy number variations (CNVs), but the epigenetic aberrations that are associated with clinical prognosis and therapeutic failure remain not completely identify. In the present study, a total of 55 lung cancer patients were included and we conducted genomic and genetic expression analyses, immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 49 publications
(76 reference statements)
4
25
0
Order By: Relevance
“…The prevalence and mortality rates of lung cancer have increased worldwide (1)(2)(3). The detection and pathological research of lung cancer are important in the diagnosis and therapy of cancer diseases (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence and mortality rates of lung cancer have increased worldwide (1)(2)(3). The detection and pathological research of lung cancer are important in the diagnosis and therapy of cancer diseases (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that overexpression of miR-122-3p suppressed lung cancer cell proliferation. Subsequently, 5-bromo-2-deoxyuridine (BrdU) staining assay 3 cells/well) were seeded onto a 96-well plate and cultured with 400 µl antibiotic-free DMEM. Then, the mixture was added to the cell culture plates and incubated at 37˚C in 5% CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that HDAC9 is a TF that is closely related to the RBM8A-mediated regulation of OXA resistance in HCC. Abnormally high HDAC9 expression has been shown to be closely related to malignant biological behaviors such as proliferation, invasion and metastasis in various tumors [41][42][43][44][45]. In recent years, a variety of HDAC inhibitors have been widely used in basic research and clinical anticancer treatment [46,47], representing a current research hotspot.…”
Section: Rbm8a (Y 14)mentioning
confidence: 99%
“…51 This findings suggest the importance of the three main epigenetic mechanisms, DNA methylation, histone code modifications and chromatin remodeling complexes in cancer progression (table I and II). [52][53][54][55][56][57][58] Along with, overexpression of BRG1 and BRM in the cisplatin toxicity, 50 or doxorubicin chemo resistance mechanisms associated with the expression of the subunits SMARCB1 and SMARCA4 (BRG1) in front to NSCLC cells. 51 All of that, suggesting the importance of the three main epigenetic mechanisms DNA methylation, histone code modifications and chromatin remodeling complexes in cancer progression and potential new oncological therapeutic strategies in NSCLC, all of which have been shown in…”
Section: Epigenetics Therapeutics In Nsclcmentioning
confidence: 99%
“…21 In particular, Van Den Broeck and colleagues in 2008, have identified that trimethylation state in lysine 20 of histone H4 (H4K20me3) allows the prognosis stratification of AD-NSCLC patients with higher risk of death in clinical stage I. H4K20me3 has additionally been proposed as biomarker in subgroups of AD patients with poor differential clinical prognosis, and potentially determinant for the use of adjuvant chemotherapy. 71 Additionally, while low levels of the histone mark H3K27me3 have been associated with chemo resistance and poor prognosis in NSCLC patients, 56 additional reports have confirmed that higher expression of H3K27me3 correlates with better overall survival (OS) and better prognosis, redefining subgroups of NSCLC patients with an epigenetic phenotype and different clinical outcome. 72 Additionally, despite histone marks H3K4me2, H2AK5ac and H3K9ac are related to global and diseasefree survival in early clinical stages of NSCLC patients, undergoing curative surgical resection.…”
Section: Histone Code Modifications In Nsclcmentioning
confidence: 99%